Fractional Calculus of Variations in Terms of a Generalized Fractional Integral with Applications to Physics. (13th May 2012) - Odzijewicz, Tatiana; Malinowska, Agnieszka B.; Torres, Delfim F. M.
Abstract : We study fractional variational problems in terms of a generalized fractional integral with Lagrangians depending on classical derivatives, generalized fractional integrals and derivatives. We obtain necessary optimality conditions for the basic and isoperimetric problems, as well as natural boundary conditions for free-boundary value problems. The fractional action-like variational approach (FALVA) is extended and some applications to physics discussed.